Impact of cannabis consumption on the course of bipolar disorder. (13th April 2021) - Brahim, S.; Aoun, M.H.; Boukhchina, R.; Frej, S. Ben; Henia, M.; Zarrouk, L.
Abstract : Introduction: Although one third of patients with Bipolar Disorder have an addiction to Cannabis or an abused consumption, the interaction between cannabis use and bipolar disorder remains controversial. Objectives: To evaluate the use of cannabis among patients with Bipolar Disorder and to compare the socio-demographic and clinical characteristics between patients who are consumers and non-consumers. Methods: This is a retrospective, descriptive study including all patients treated for type I bipolar disorder in the psychiatric department of Tahar Sfar Hospital of Mahdia (Tunisia). In addition to socio-demographic and clinical characteristics, we collected data on cannabis use (age at first consumption and frequency of consumption). Results: Our study population consisted of 84 male patients followed for bipolar I disorder. The mean age was 36.8 ± 11.3 years. Among these patients, 23 (27.8%) had regular cannabis use. The average age at first consumption was 21.6 ± 7.2 years. Bipolar patients with regular cannabis consumption had an earlier age of onset of the disorder (p = 0.02). They had higher numbers of manic episodes (p = 0.05), higher number of manic episodes with severe intensity (p = 0.04), higher number of manic episodes with mixed characteristics(p = 0.04), a higher number of hospitalizations (p = 0.01) with longer hospital stays (p = 0.02). Conclusions: Cannabis use among patients with type 1 bipolar disorder is associated with an unfavorable course of the disorder. Early diagnosis and appropriate management of this comorbidity seem to be essential for improving the prognosis of bipolar disorder.